Comparison of the effects of growth regulators on in vitro regeneration of ridge gourd and sponge gourd through shoot - Nahar, E; Haque, ME; Sikdar, B (Journal of Bio-Science, 2011)
Context: Luffa cylindrica and Luffa acutangula are highly cross pollinated crops and propagated mainly by seeds. Genetic stability cannot be maintained easily by seed propagation. It can be maintain by developing special vegetative technique through tissue culture. Objectives: To compare the effects of growth regulators between two species of Luffa using shoot tips for develop the rapid, simple and efficient in vitro regeneration protocol. Materials and Methods: Shoot tips used were collected from in vivo grown plants. They were excised from plants and surface sterilized by HgCl2 treatment. The isolated tips were cultured on semisolid MS medium supplemented with different concentrations and combinations of different growth regulators. Results: The highest result of direct shoot multiplication of ridge gourd was observed using 2 mg/l BAP + 0.2 mg/l GA and in case of sponge gourd it was 1.5 mg/l BAP. For callus induction significant result was found using 4 mg/l BAP + 0.2 mg/l NAA in ridge gourd and 3 mg/l BAP + 0.2 mg/l NAA in sponge gourd. Indirect regeneration was performed by subculturing organogenic callus of sponge gourd on MS with 1.5 mg/l BAP + 0.2 mg/l GA3 and the callus of ridged gourd on MS + 1.5 mg/l BAP + 0.2 mg/l NAA + 0.2 mg/l nicotinic acid. Regenerated shoots of both species were rooted well on MS containing NAA at low concentration. Conclusion: Hormonal differences and simple rapid in vitro regeneration protocol of L. cylindrica and L. acutangula have been established. Keywords: Growth regulators; in vitro regeneration; ridge gourd; sponge gourd. DOI: http://dx.doi.org/10.3329/jbs.v18i0.8781 JBS 2010; 18(0): 88-93